Characteristics of Children Cared for by a Physician-Staffed Helicopter Emergency Medical Service. Issue 7 (July 2021) - Enomoto, Yuki; Tsuchiya, Asuka; Tsutsumi, Yusuke; Kikuchi, Hitoshi; Ishigami, Koji; Osone, Junpei; Togo, Masahito; Yasuda, Susumu; Inoue, Yoshiaki
Abstract : Objectives: The effectiveness of Japanese helicopter emergency medical services (HEMS) and interventions at the scene is not clear as regard children. For effective use of HEMS at the clinical scene, we need to clarify the characteristics of pediatric patients cared for by HEMS. Therefore, the objective of this study was to describe the characteristics of pediatric scene flights and to describe the procedures performed on the patients. Methods: This was a retrospective cohort study based on the database for children aged younger than 18 years who were cared for by physician-staffed HEMS of Ibaraki prefecture, in Japan. We reviewed the database for air medical transports conducted at our institution from July 2010 to December 2016. Results: During the 6.5-year period, the Ibaraki HEMS attended to 288 children. The median age of the children was 11 (interquartile range, 5–14) years. Of the total, 196 (68.1%) of the children had trauma-related injuries. The head was the most common site of significant injuries (12.4%). The most common cause of nontrauma incidents was seizure (9.0%). In 65.9% of the patients, the injury or illness was of mild or moderate severity at the scene. An intervention was applied at the scene in 76.0% of the cases: 75.1%, intravenous route; 6.9%, intubation; and 13.4%, drug administration. Of those patients, 29.1% were discharged from the emergency department. In-hospital mortality accounted for 1.5% (n = 2) of the cases. Conclusions: Although the condition at the scene of most of the pediatric patients transported by the physician-staffed HEMS was not severe, an intervention was frequently applied from the scene. Improving the dispatch criteria and monitoring compliance are needed for appropriate use of HEMS.